Gambaran Efikasi Diri Pasien yang Menjalani Hemodialisis - Devia Putri Lenggogeni; Hema Malini; Rika Fatmadona; Ega Silvia Roza (Universitas Batanghari Jambi, 2021)
Self-efficacy is an individual's perception of their ability in carrying out of action. Self- efficacy is required by end-stage renal disease patients undergoing hemodialysis to be able to carry out good self-management. This research was using a descriptive design. The number of samples used in this study amounted to 63 people. Sampling was done by consecutive sampling technique. Data was collected by using Chronic Kidney Disease Self Efficacy (CKD-SE) questionnaire. Based on this study was known that the largest age range is 41-60 years (66,7%), the most respondent is male (60.3%), the most respondent is still working (61.9%), the most etiology of end stage renal disease is hypertensive renal disease (52.4%), the highest education of respondents is senior high school (47.6%), duration hemodialysis is < 12 months (71.4%). The mean score of self-efficacy was 72.25. The highest sub-variable of self-efficacy is autonomy which a mean score 23.51. Self-efficacy assessment using CKD-SE can be used in patients undergoing hemodialysis. Knowing self-efficacy can help a nurse to educate patients, so that will improve self-management patients undergoing hemodialysis.